Employment Protection and Gender Dysphoria: Legal Definitions of Unequal Treatment on the Basis of Sex and Disability - Remmers, Cynthia Lark (1979)
Transsexuality, also known as gender dysphoria syndrome, has only recently been recognized as a legitimate medical entity that may be treated by reassignment surgery and psychological therapy. This Article traces the development of this recognition by the medical profession and outlines the social and legal issues still facing transsexuals, focusing on employment discrimination. State and federal decisions based on sex discrimination statutes have proven unsatisfactory to protect transsexuals. The authors contend that sex discrimination statutes should be interpreted to protect transsexuals and suggest two alternative approaches, based on constitutional theories and statutes designed to protect handicapped individuals, that may better serve to secure employment rights for transsexuals